Technological and digital literacy challenges in implementing flipped learning: insights from Eastern Indonesia - Haerazi Haerazi; Lalu Ari Irawan; Rimajon Sotlikova; Moti Alemayehu (Institute of Advanced Engineering and Science, 2026)
This study explores the challenges faced by English as a foreign language (EFL) learners and teachers in Eastern Indonesia when implementing flipped learning, with a focus on technological access and digital literacy. Despite the potential benefits of flipped learning, such as increased learner autonomy and deeper cognitive engagement, these factors significantly hinder its effectiveness in under-resourced regions. The study employs a qualitative research design, utilizing interviews and questionnaires with 199 EFL learners and 10 certified EFL teachers from both West and East Nusa Tenggara. The findings reveal that limited internet access, lack of personal digital devices, and low digital literacy are the primary obstacles to successful engagement with flipped learning. These challenges prevent learners and teachers from adequately preparing for class, leading to reduced participation in interactive activities and ultimately hindering language acquisition for learners. In response, the study proposes strategies such as improving internet and device access, offering digital literacy training, and adopting a blended learning approach that combines both online and face-to-face learning. The study contributes to the existing literature by providing context-specific insights into the barriers faced by EFL learners in Indonesia and offering practical recommendations for overcoming these challenges to improve the efficacy of flipped learning in similar educational settings.